OPTICAL CHARACTERISTICS OF GAS-DISCHARGE PLASMA IN MIXTURES OF MERCURY DIBROMIDE VAPOR WITH GASES - ANTONINA MALININA (CAMBRIDGE SCHOLARS PUBLIS, 2020)
This volume presents the results of a number of studies on the spectral, integral and temporal characteristics of radiation and DBD plasma parameters on mixtures of mercury dibromide vapor and gases such as helium, argon, neon, xenon, krypton, nitrogen, and sulfur hexafluoride. Gas-discharge plasma in such mixtures is used as a working medium for exciplex sources of pulsed-periodic coherent lasers and spontaneous radiation (excilamps) in a blue-green spectral region with a wavelength at a maximum intensity equal to 502 nm. Such radiation sources attract the attention of researchers due to the.